IMPLEMENTASI SISTEM DIAGNOSIS LAYANAN INTERNET PT. FIBER NETWORKS INDONESIA MENGGUNAKAN METODE CERTAINTY FACTOR DAN CASE-BASED REASONING - Jeffry Andhika Putra; Teguh Sadewo Pangestu (Indonesian Journal of Business Intelligence (IJUBI), 2022)
PT. Fiber Networks Indonesia (FiberNet) is intended to make it easier for service users to overcome FiberNet service disruptions. So, users can directly diagnose symptoms and the system directly provides solutions related to service problems. It is hoped that the system can help users and provide education in solving problems without contacting customer service. The FiberNet service fault diagnosis system is designed and implemented using PHP, MySQL database, Certainty Factor method, and Case-Based Reasoning method. The application of the Certainty Factor method is used to determine the percentage value based on the specified confidence value. The application of the Case-Based Reasoning method is used to compare new cases, old cases, and determine the case of each selected symptom where the highest Certainty Factor percentage value becomes a reference. The application made has five elements of an expert system, namely a knowledge base, database, inference mechanism, user interface, and system implementation where the application can detect symptoms experienced in internet services.